A dual radio approach for efficient communication in mobile telemedicine environments - Mukhopadhyay, Adwitiya; HR, Rakshitha; Goswami, Purnendu (International Journal of Engineering and Technology, 2018)
Telemedicine technology provides patients with an effective healthcare system that complements other healthcare systems that already exist. Two different ways of implementing telemedicine systems are, (i) In a stationary environment, from a clinic in a village to a distant hospital. (ii) In a mobile environment where we connect from a moving ambulance to a remote hospital. This paper considers the latter scenario. In such a situation, the transmission of biosignals and sometimes multimedia data is required for critical patient diagnosis. We have designed a simulation scenario where Blood pressure (BP) signals are being transmitted along with streaming audio. However, we have used different radio access technologies for the purpose. BP is sent over WiFi and audio over LTE. This is done since WiFi connectivity is intermittent in a highway road network and as BP is transmitted infrequently, this serves the purpose. The LTE channel is kept free to transmit streaming audio signals. We have considered Vehicular Ad-Hoc Network (VANET) without considering any roadside infrastructure. In VANET the communication from source to destination is established using vehicle to vehicle communication. While transferring the patient from the emergency location, the ambulance makes use of the vehicular network for transmission of the relevant data. A novel attempt has been made to leverage the presence of multiple wireless technologies such as WiFi and LTE.Â Â
Keywords: Telemedicine; VANET; LTE; Wi-Fi; AODV; NS3.